Analisis Makna Gramatikal pada Kumpulan Puisi Perihal Gendis Karya Sapardi Djoko Damono sebagai Alternatif Bahan Ajar di Sekolah Menengah Atas - Sumarno; Sari, Purna (Edukasi Lingua Sastra, 2024)
Problem research this the grammatical meaning on the poetry collection Perihal Gendis by Sapardi Djoko Damono as an alternative teaching material in high schools. The aim of this research is to describe the grammatical meaning of the poetry collection Perihal Gendis by Sapardi Djoko Damono as an alternative teaching material in high schools. The method in this research is a descriptive method with a qualitative approach. This method is adapted to the research objective, namely to describe the types of grammatical meaning in the poetry collection Perihal Gendis by Sapardi Djoko Damono as an alternative teaching material in high school. The results of the research that there is carried out are available 60 quotes grammatical meaning on the poetry collection Perihal Gendis. The grammatical meaning consists of 34 quotations of the type of grammatical meaning of affixation, 14 quotations of the type of grammatical meaning of reduplication, and 12 quotations of the type of grammatical meaning of composition. From three types grammatical meaning most found type affixation gramatical meaning. Based on the objectives of learning Indonesian language and literature, this collection of poetry can be used as an alternative teaching material in high school. This collection of poems Perihal Gendis by Sapardi Djoko Damono meets the criteria for teaching materials and provides positive benefits for students. Teachers can use collection of poems Perihal Gendis by Sapardi Djoko Damono as an alternative for learning grammatical meaning. Based on linguistic, psychological and cultural background aspects of students, this collection of poetry can be used as an alternative teaching material for learning Indonesian in high school.